Information Systems and Administrative Decision Support: - (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Information has become a key resource to manage modern businesses. This is because the business world of today is fluid, dynamic, turbulent and demands for accurate, relevant, timely, complete and inexpensive information to drive the decision making process to enhance organization’s capacity to manage opportunities and threats. MIS works with a medium processing speed in online mode. In general, low-level administration is utilized. The decision-making support system provides a significant instrument for companies, managers and other top authorities to decide the problem. Management Information Systems is a valuable tool which allows managers to make accurate decisions and give structured and summarized information to decision makers in a timely manner. In the study, the idea, features, MIS kinds and MIS model are discussed, and the influence and function of MIS in decision-making are highlighted in especially. There are several IT systems such as TPS, DAS, KWS, MIS, DSS, ES, CSCWS, GDSS and ESS in today's corporate sector. In organizational structure and decision-making, each has a distinctive role. Two key information systems were picked by the authors in this paper, MIS and DSS. After the discussion on each idea of the decision-making process, the features, relationships and linkages of each idea to the decision-making process were established. At the same time, the discussions will be enhanced and the position of each MIS and DSS information system in the corporate decision making will be clearly illustrated by various model and figures.